2012
DOI: 10.1016/j.ccr.2012.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Targeting of the Cyclin D3:CDK4/6 Complex in T Cell Leukemia

Abstract: SUMMARY D-type cyclins form complexes with cyclin dependent kinases (CDK4/6), and promote cell cycle progression. Although cyclin D functions appear largely tissue specific, we demonstrate that cyclin D3 has unique functions in lymphocyte development and cannot be replaced by cyclin D2, which is also expressed during blood differentiation. We show that only combined deletion of p27Kip1 and Rb is sufficient to rescue the development of Ccnd3−/− thymocytes. Furthermore, we show that a small molecule targeting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
130
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(135 citation statements)
references
References 49 publications
5
130
0
Order By: Relevance
“…Cdk4/6 inhibitors also have pRB-independent effects, particularly when used at high concentrations. In contexts where deregulation of Cyclin D:Cdk4/6 kinases drives tumorigenesis, inhibition of these kinases can trigger cellular senescence or apoptosis (Fry et al 2004;Thangavel et al 2011;Choi et al 2012;Sawai et al 2012). Cdk4/6 inhibitors had modest effects when tested as a monotherapy in solid tumors (Flaherty et al 2012;Dickson et al 2013;Cadoo et al 2014;DeMichele et al 2015;Vaughn et al 2015).…”
Section: The Translation Of Rb Researchmentioning
confidence: 99%
“…Cdk4/6 inhibitors also have pRB-independent effects, particularly when used at high concentrations. In contexts where deregulation of Cyclin D:Cdk4/6 kinases drives tumorigenesis, inhibition of these kinases can trigger cellular senescence or apoptosis (Fry et al 2004;Thangavel et al 2011;Choi et al 2012;Sawai et al 2012). Cdk4/6 inhibitors had modest effects when tested as a monotherapy in solid tumors (Flaherty et al 2012;Dickson et al 2013;Cadoo et al 2014;DeMichele et al 2015;Vaughn et al 2015).…”
Section: The Translation Of Rb Researchmentioning
confidence: 99%
“…Cyclin D3 is an essential D-type cyclin for normal expansion of T-cell progenitors (18). Cyclin D2 and D3 have nonredundant roles in T-cell development (29). Cyclin D3 deficiency is sufficient to reduce susceptibility to T-cell malignancies.…”
Section: Inactivation Of Mtorc1 Prevents Oncogenic Kras-induced T-allmentioning
confidence: 99%
“…Due to this synthetic-lethal interaction between NOTCH1 overexpression and CDK6 inhibition, it was proposed that inhibiting the kinase activity of CDK6 in patients with NOTCH1-postive T-ALL is an attractive therapeutic strategy. [65][66][67] Furthermore, several studies on patients suffering from lymphomas have revealed chromosomal translocations and the consequent over-expression of CDK6 is a driving force for the disease. 68,69 Taken together, these findings strongly support CDK6 as a specific therapeutic target in human lymphoid malignancies.…”
Section: Introductionmentioning
confidence: 99%